Konsumsi Konten Virtual di Kalangan Generasi Z: Perspektif Penghayat Kepercayaan - Heilya Nediva; Masni Marshanda Butar Butar (Jurnal Riset Rumpun Agama dan Filsafat, 2026)
The development of digital technology has transformed information consumption patterns, including within the realm of spiritual belief. Generation Z, as the generation born and raised in a digital world the digital ecosystem, exhibits new tendencies in understanding and internalizing noble values through various digital platforms. This study aims to analyze the consumption patterns of virtual content among Generation Z from the perspective of adherents of indigenous beliefs in the One Supreme God (Penghayat Kepercayaan terhadap Tuhan Yang Maha Esa), and to examine its implications for modern forms of spirituality. The method used in this study is a literature review with a descriptive qualitative approach, focusing on theoretical studies concerning digital religiosity, media literacy, and spiritual individualization. The results of the study show that digital media, especially platforms like YouTube, Instagram, and Podcasts, have become an alternative space for Generation Z to explore and express spiritual values independently, interactively, and contextually. This phenomenon also presents challenges in the form of the spread of unverified information and the potential to distort facts regarding the authenticity of the teachings of the belief. Therefore, spiritual digital literacy is needed to guide Generation Z to remain critical, rational, and selective in consuming religious content in the digital space.